Inverse Problem to Constrain Hydraulic and Thermal Parameters Inducing Anomalous Heat Flow in the Lower Yarmouk Gorge. (November 2016) - Goretzki, Nora; Inbar, Nimrod; Kühn, Michael; Möller, Peter; Rosenthal, Eliyahu; Schneider, Michael; Siebert, Christian; Raggad, Marwan; Magri, Fabien
Abstract: In the present study, inverse problems (IP) are applied with FEPEST ® in FEFLOW ® to find parameter distributions of hydraulic and thermal conductivity that lead to the observed thermal anomalies in the Lower Yarmouk Gorge (LYG) and a more accurate fit of borehole data. Results indicate reduced hydraulic conductivities in shallower parts of the system than previously estimated. The absence of a fault under the Lower Yarmouk Gorge in deeper sediments can be superseded by presence of interconnecting local fractures. The contribution of the conductive thermal regime turns out to be negligible.